A block queueing network model for control patients flow congestion in urban healthcare system. (15th January 2013) - Song, Jie; Chen, Weiwei; Wang, Longfei
Community healthcare service plays a very important role in China's urban hierarchical healthcare service system. Because of the irrational distribution of current patient flow, long patient waiting time in general hospitals and the low utilisation of the community healthcare facilities are crucial problems in China's healthcare delivery system. In this paper, a block queueing model with batch size service is developed to model patient flow congestion. Within the model, an incentive rule for referral patients is used to improve patients flow. Results of the mathematical model showed that the waiting time of the referral patients who were from community health centres was effectively shortened if they were given a priorities incentive rule.